Explaining older consumers' low use of the internet - Jul Thanasrivanitchai (2018)
© 2017 Inderscience Enterprises Ltd. Many studies show that the usage rate of the internet by older adults is the lowest of any demographic group. This paper explores the reasons for older adults' lower inclination to use the internet by employing control theory. The theory suggests that as people increasingly experience 'losses' with age they also experience loss of control of their environments, including technology. Secondary control strategies, which allow the individual to protect himself or herself from the perceived negative consequences associated with the older persons' inability to control their technological environment, may help explain their low propensity to adopt and make use of the internet. Findings based on a large-scale study in Thailand suggest that secondary control may provide an explanation for the low rates of internet adoption and usage among older consumers. Implications for theory and practice are offered and directions for future research are suggested.